Family Nursing Care to Improve Self Care in Stunting Prevention: A Systematic Literature Review - Nasution, Nurhafizah; Sansuwito, Tukimin Bin (International Journal of Health Sciences, 2024)
Stunting affects approximately 22.3% of children under five globally, with higher prevalence in low- and middle-income countries. While family nursing interventions may play a crucial role in preventing stunting through improved self-care practices, comprehensive evidence synthesis is lacking. This systematic review aimed to evaluate the effectiveness of family nursing care interventions in improving self-care practices related to stunting prevention, identify successful strategies, analyze outcomes, and provide evidence-based recommendations for healthcare practitioners.Following PRISMA 2020 guidelines, we systematically searched PubMed/MEDLINE, Scopus, CINAHL, and Science Direct for studies published between 2019 and 2024. Two independent reviewers assessed methodological quality using standardized tools. Data were synthesized narratively due to intervention heterogeneity. Twenty-five studies met inclusion criteria, including mixed-methods, quantitative observational, randomized controlled trials, and qualitative studies. Family nursing interventions improved health literacy (35.4% increase) and growth monitoring compliance (68.5% increase). Culturally adapted educational approaches and home-based support showed the most substantial evidence for effectiveness. Stunting prevalence decreased by 17.5% among intervention groups, with improved height-for-age Z-scores (mean improvement: 0.45 SD). Success factors included cultural competency, regular supervision, and clear intervention protocols.Conclusion: Family nursing interventions effectively improve self-care practices and contribute to stunting prevention when incorporating cultural adaptation, regular monitoring, and integrated community support. Future research should focus on long-term outcomes and standardized measurement tools across diverse settings.